Optimizing study to boost performance and well-being: A study-crafting scoping review - Palacios-Pedrero, Noah; Cortés-Denia, Daniel; Lopez-Zafra, Esther (Journal of University Teaching and Learning Practice, 2025)
As higher education students confront increasing challenges that hinder their well-being and performance, study strategies grow on importance. Drawing from the job-crafting approach, and the job and study demands-resources theories, study-crafting is highlighted as a potentially useful strategy to adapt the study environment to each student’s needs and characteristics. Following the PRISMA-ScR model (2018), the present scoping review charts what is known about crafting strategies applied by students, aiming to assess how study-crafting has been operationalized, its antecedents and effects. A search of empirical peer-reviewed articles concerning students, was conducted at the Web of Science (WoS) and PsycINFO platforms up to January 2025. In total, 579 registers were considered, of which 10 papers were included for the final review after a selection process. Results underline different trends on the measure and operationalization of study-crafting; study demands and resources, engagement, positive emotions, daily events, and teachers’ authentic leadership are highlighted as possible antecedents of study-crafting; and identify beneficial associations of study-crafting with academic performance (improving engagement, work-school facilitation, study-to-sports spillover, and creativity) and with mental health (improving well-being, quality of university life, and positive affect; and reducing emotional exhaustion). All in all, study-crafting is emphasized as a potentially useful construct on which to intervene to foster academic performance and well-being of students at higher education. Further results, limitations, and implications are discussed.